Toothache Relief Using Toob: An Investigation of Folk Medicine in Siquijor Island, Philippines - Bucol, Abner A. (Silliman Journal, 2022)
Toob is practiced by a folk healer or herbolario in Siquijor Island in Central Philippines as means of curing toothache, utilizing the smoke from the heated seeds of the herb Datura metel (locally katyubong) and fine roots of unidentified herbs and shrubs.